2010
DOI: 10.1086/649588
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Vitamin A Receptor and Innate Immunity Genes Influence the Antibody Response to Rubella Vaccination

Abstract: Background Genetic polymorphisms play an important role in rubella vaccine-induced immunity. Methods We genotyped 714 healthy children after two age-appropriate doses of rubella-containing vaccine for 142 potential SNPs. Results Specific polymorphisms in the vitamin A receptor, RIG-I, TRIM5 and TRIM22 genes were significantly associated with rubella vaccine humoral immunity. The minor allele of the rs4416353 in the vitamin A receptor gene was associated with an allele dose-related decrease (P=.019) in rube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 43 publications
2
77
1
Order By: Relevance
“…Our association study determined that the non-synonymous SNP rs3740996 in the TRIM5 gene was associated with rubella-specific antibody response (p=0.01). This specific SNP was found to have an important functional role (29)(30)(31). This same study also found 22 important associations (range of p values 0.002-0.05) between genetic variants in the vitamin A receptor family (RARA, RARB, and RARG), vitamin D receptor, RXRA genes, and rubella-specific (IFN-γ, IL-2, IL-10, TNF-α, and GM-CSF) cytokine responses (32).…”
Section: Innate Gene Polymorphisms and Vaccine Immunitymentioning
confidence: 54%
See 2 more Smart Citations
“…Our association study determined that the non-synonymous SNP rs3740996 in the TRIM5 gene was associated with rubella-specific antibody response (p=0.01). This specific SNP was found to have an important functional role (29)(30)(31). This same study also found 22 important associations (range of p values 0.002-0.05) between genetic variants in the vitamin A receptor family (RARA, RARB, and RARG), vitamin D receptor, RXRA genes, and rubella-specific (IFN-γ, IL-2, IL-10, TNF-α, and GM-CSF) cytokine responses (32).…”
Section: Innate Gene Polymorphisms and Vaccine Immunitymentioning
confidence: 54%
“…We studied the association of polymorphisms in these candidate innate IR genes to rubella vaccine-induced humoral and cellular immune responses. Overall, eight significant SNP associations (p<0.05) were found between the vitamin A (RARB), RIG-I, and TRIM (TRIM 5 and TRIM 22) genes and humoral immunity after rubella vaccine (29). Our association study determined that the non-synonymous SNP rs3740996 in the TRIM5 gene was associated with rubella-specific antibody response (p=0.01).…”
Section: Innate Gene Polymorphisms and Vaccine Immunitymentioning
confidence: 79%
See 1 more Smart Citation
“…Innate immunity also takes part in the response to viral pathogens, playing an important role in the initiation and modulation of adaptive immunity. For this reason, SNP associations were identified between the vitamin A (RARA, RARB, and RARG), RIG-I/DDX58, and TRIM genes and rubella vaccine-specific immunity (Ovsyannikova et al, 2010a(Ovsyannikova et al, , 2010b. Notably, the coding TRIM5 SNPs rs3740996 (previously found to affect TRIM5 antiviral activity) (Goldschmidt et al, 2006;Javanbakht et al, 2006;Sawyer et al, 2006;van Manen et al, 2008), rs3740996, and rs10838525 were associated with variations in rubella-specific humoral immunity, tumor necrosis factor (TNF)-a secretion, and IL-2/ GM-CSF production, respectively.…”
Section: The Case Of Immune Response Heterogeneity To Vaccinesmentioning
confidence: 99%
“…Upon review of the data flagged by these thresholds, we are able to assess whether the interpolated value is likely to be an appropriate estimate of an individual's rubella virus-specific neutralizing antibody titers and therefore to decide whether or not it is appropriate to include the data in analyses. We have previously reported rubella virus-specific IgG levels using Beckman Coulter's Access Rubella IgG assay (12,(26)(27)(28)(29)(30). This assay calculates anti-rubella virus (strain HPV-77) titers based on a standard curve calibrated against the WHO 2nd International Standard Preparation for Anti-Rubella Serum.…”
Section: Fig 1 Distribution Of Initial Nt 50 Values Estimated As Thementioning
confidence: 99%